Dialogics, Diacritics, Diasporics: Ranjan Ghosh, J. Hillis Miller, and the Becoming-Now of Theory. Issue 3 (December 2017) - Margaroni, Maria
Abstract : My aim in this essay is to reflect on the compelling dialogic project undertaken by Ranjan Ghosh and J. Hillis Miller in Thinking Literature Across Continents, focusing in particular on its implications for contemporary literary theory. Situating this project within a wider philosophical tradition that invests in dialogue as the textual space where theorein is the product of a synergic as much as conflictual endeavor, I argue that the Ghosh-Miller exchange across continents performs the becoming-Now of literary theory. In other words, I suggest that the dialogic encounter among more-than-one voices in this book reclaims the immanent doing of theory and cultivates a world-concerned thinking that diverges from dominant paradigms of theoria as the experience of an inevitable belatedness. Reading for the silences and tensions in the intimate, entangled becoming staged by the Ghosh-Miller book, I demonstrate how the process of worlding in the literary field can unfold in a minor mode, introducing hermeneutic possibilities that deterritorialise Angloglobalism and diffractively infringe habituated colonial traditions.